39th Annual IEEE Conference on Local Computer Networks 2014
DOI: 10.1109/lcn.2014.6925784
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of denial-of-service attacks on wireless sensor networks

Abstract: Wireless sensor networks (WSNs) are especially susceptible to denial-of-service attacks due to the resourceconstrained nature of motes. We follow a systematic approach to analyze the impacts of these attacks on the network behavior; therefore, we first identify a large number of metrics easily obtained and calculated without incurring too much overhead. Next, we statistically test these metrics to assess whether they exhibit significantly different values under attack when compared to those of the baseline ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A linear regression model is applied to predict energy consumption and deployed results under the denial-ofservice attacks. Consider flooding can be detected with high accuracy while keeping the number of false positives very low [14]. Consider the importance of the security of networks.…”
Section: Mobile Agents Based Ids In Wsnsmentioning
confidence: 99%
“…A linear regression model is applied to predict energy consumption and deployed results under the denial-ofservice attacks. Consider flooding can be detected with high accuracy while keeping the number of false positives very low [14]. Consider the importance of the security of networks.…”
Section: Mobile Agents Based Ids In Wsnsmentioning
confidence: 99%
“…However, it is an extremely costly solution for resource-constrained networks. Riecker et al [4] measured the impact of Denial-of-Service Attacks: Jamming and Blackhole, using a testbed consisting of TelosB motes. The authors identified the performance metrics classes based on their capability to detect attacks.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in [20], the authors show authentication mechanisms to legitimate primary users from the available spectrum usage by means of physical layer network coding techniques. In [21], the authors focus on jamming and blackhole attacks. They propose a mechanism based on a 2…”
Section: Introductionmentioning
confidence: 99%
“…However, no cognitive radio is considered. In contrast to [21], we propose a mathematical model as a tool for attack detection instead of practical measurements on the system's performance. The mathematical analysis is more tractable than measuring the system operation in normal conditions.…”
Section: Introductionmentioning
confidence: 99%